O stresie w różnorodnych przestrzeniach życiowych nastolatków w kontekście ich seksualności - Rojewska, Ewa (Studia Edukacyjne, 2020)
Bearing in mind the meaning of sexuality for the quality of human life, adolescence as a vulnerable period and the attendant risks, the main issue of interest in this text is stress in various areas of life of adolescents in the context of their sexuality. The first part of the article focuses on young people’s sexuality on the basis of relevant literature, while the further part of the study presents methodological assumptions. The third part of the work is dedicated to the analysis of the examination results. The article ends with the conclusions made on the basis of the research results.